A Survey of Knowledge and Practices Regarding Prevention of Unintended Pregnancies. Issue 1 (March 2015) - Brown, Gina; Parham, Douglas F.; Harris, Lauren; Dare, Megan R.; Dollmann, Leanna
Abstract : Purpose: The purpose of this study was to identify the gaps in Kansas physician assistant practices and knowledge regarding prevention of unintended pregnancies with the aim of reducing the unintended pregnancy rate. Methods: A survey targeting all licensed physician assistants in Kansas (N = 733) was developed based on a literature review of contraceptive behaviors, unintended pregnancy data, and providers' practices. Results: The response rate was 22%. Most knowledge questions were answered incorrectly, with almost 60% of respondents underestimating the percent of both unintended pregnancies and abortions resulting from them. Eighty percent did not know that abstinence among teenagers is increasing. An average of only 28% of respondents frequently counseled teens to get contraception before their first intercourse, and counseling about highly effective reversible contraception beyond oral contraceptives was limited. Only 13% reported having been trained in intrauterine device (IUD) insertion. Of the physician assistant respondents who prescribe oral contraceptives, 42% reported ordering a 1-month supply for patients, despite risk of usage gaps. Conclusions: Areas where Kansas physician assistants could improve were identified. Increased counseling of teenagers about (a) highly effective methods of contraception and (b) contraception before their first intercourse is recommended. Training physician assistants in IUD insertion and prescribing oral contraceptives to dispense multiple months at once could result in fewer unintended pregnancies.